La problemática concejil en El Bierzo durante la crisis del Antiguo Régimen: los enfrentamientos antiseñoriales e interconcejiles (Estudios humanísticos. Geografía, historia y arte, 1998)
This research analyses the degree of hostility towards the aristocracy/ landowning class and the rivalry amongst parish councils in the Bierzo province of León, Spain. It is based on the study of legal documents and takes in the period comprising the crisis of the Ancien Regime (1800-1850).Both the low level of anti-aristocratic feeling and the small number of disputes amongst the councils are casily seen, the latter usually caused by conflicts concerning pastureland or rights to water.